2022
DOI: 10.1007/s00894-022-05088-w
|View full text |Cite
|
Sign up to set email alerts
|

DFT analysis of valproic acid adsorption onto Al12/B12-N12/P12 nanocages with solvent effects

Abstract: Using density functional theory, the adsorption of valproic acid onto the surface of fullerene-like nanocages was investigated. Valproic acid interact the nanocages through the carboxylic group with energies of -144.14, -109.71, -105.22 and -84.96 kcal/mol. The FMOs energy levels were considerably altered upon adsorption, resulting in a reduction in energy gap and increase in electrical conductivity. This suggests that nanocages could be used as sensors as well as options for drug administration in biological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In addition, the thermodynamic properties of the investigated structures were analyzed to determine whether they were thermodynamically stable. 59 The computed Gibbs energies indicated that PA is spontaneously adsorbed on the metal-SiO 2 shell. Moreover, different Ag/Au–SiO 2 showed distinct thermodynamic properties.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, the thermodynamic properties of the investigated structures were analyzed to determine whether they were thermodynamically stable. 59 The computed Gibbs energies indicated that PA is spontaneously adsorbed on the metal-SiO 2 shell. Moreover, different Ag/Au–SiO 2 showed distinct thermodynamic properties.…”
Section: Resultsmentioning
confidence: 96%
“…The negative value of the enthalpy (ΔH < 0) indicates that the reaction is exothermic. If ΔH > 0, the reaction is said to be an endothermic reaction [ 46 ]. The negative value of Gibbs free energy (ΔG < 0) represents the spontaneous adsorption of the TPOXX molecule on the metal-loaded silica nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the 6-31G (d,p) basis set, MB and AA were optimized using DFT with the B3LYP functional (44) . All the calculations were done in Gaussian 09 after the file was terminated normally, and the result files/log files were analyzed again in Gauss view 6.0 . The optimized structures were calculated from log files and the HOMO–LUMO values from CHK files .…”
Section: Methodsmentioning
confidence: 99%
“… 88 All the calculations were done in Gaussian 09 89 after the file was terminated normally, and the result files/log files were analyzed again in Gauss view 6.0. 90 The optimized structures were calculated from log files and the HOMO–LUMO values from CHK files. 91 An optimized geometry of the compounds was used to develop the MEP surface.…”
Section: Methodsmentioning
confidence: 99%